Development of water-based C-X bond formation reactions - Goh, Jeffrey (Nanyang Technological University, 2023)
The push for conducting chemical syntheses under green conditions (metal-free, room temperature, non-toxic solvent, neutral pH, no column chromatography or liquid-liquid extraction etc.) has been gaining track in recent times. By achieving this goal, we could potentially replace traditional methods which are generally exorbitant and non-environmentally friendly, thereby reducing chemical waste and valuable resources. If successful, these green synthetic strategies can be readily applied to the (1) synthesis of pharmaceuticals, (2) one-pot multi-step synthesis and (3) biomolecules functionalization. With this goal in mind, we will be able to advance the discourse on green chemical syntheses. In this thesis, we are focused on the development of a toolbox of various green synthetic methods. Henceforth, we report the development of various catalyst-free C-X bond forming reactions under green or biocompatible conditions.